1995
DOI: 10.1104/pp.109.3.907
|View full text |Cite
|
Sign up to set email alerts
|

Aging of Dry Desiccation-Tolerant Pollen Does Not Affect Protein Secondary Structure

Abstract: Protein secondary structure and membrane phase behavior i n aging Jypha latifolia pollen were studied by means of Fourier transform infrared microspectroscopy (FTIR). Membranes isolated from fresh pollen occurred mainly in the liquid crystalline phase at room temperature, whereas the membrane fluidity of aged pollen was drastically decreased. This decrease did not result i n large-scale irreversible protein aggregation, as was concluded from i n situ FTIR assessment of the amide-1 bands. Curve-fitting on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…Although group 1 and 2 LEA proteins have a much lower predicted ␣-helical content than group 3 LEA proteins, increases in ␣-helical content arising from changes in ion or sugar concentrations or hydration status could contribute to functional interactions with other biomolecules. ␣-Helical structures were found to compose approximately 40% of the overall protein secondary structures in dry cattail pollen (Wolkers and Hoekstra, 1995). Similar ␣-helical contributions to overall protein secondary structure have also been observed in maize embryos (Wolkers et al, 1998a) and carrot (Daucus carota) somatic embryos (Wolkers et al, 1998b) consistent with earlier predictions of a functional contribution of ␣-helical conformations by several LEA proteins (Dure et al, 1989;Dure, 1993).…”
Section: Potential Physiological Roles Of Pii Structuressupporting
confidence: 74%
“…Although group 1 and 2 LEA proteins have a much lower predicted ␣-helical content than group 3 LEA proteins, increases in ␣-helical content arising from changes in ion or sugar concentrations or hydration status could contribute to functional interactions with other biomolecules. ␣-Helical structures were found to compose approximately 40% of the overall protein secondary structures in dry cattail pollen (Wolkers and Hoekstra, 1995). Similar ␣-helical contributions to overall protein secondary structure have also been observed in maize embryos (Wolkers et al, 1998a) and carrot (Daucus carota) somatic embryos (Wolkers et al, 1998b) consistent with earlier predictions of a functional contribution of ␣-helical conformations by several LEA proteins (Dure et al, 1989;Dure, 1993).…”
Section: Potential Physiological Roles Of Pii Structuressupporting
confidence: 74%
“…The bands at 2928 and 2856 cm Ϫ1 represent C-H stretching vibrations, arising mainly from neutral lipids, proteins, and carbohydrates. In the 1700 to 1500 cm Ϫ1 region, the amide-I band around 1650 cm Ϫ1 and the amide-II band around 1550 cm Ϫ1 can be observed, which are attributable to proteins (Wolkers and Hoekstra, 1995). The band around 1740 cm Ϫ1 in this region is attributable to ester bonds arising from lipids.…”
Section: Protein Secondary Structure In Embryo Axesmentioning
confidence: 80%
“…FTIR spectra were recorded on a spectrometer (model 1725, Perkin-Elmer) equipped with a liquid nitrogencooled mercury/cadmium/telluride detector and a PerkinElmer microscope as described previously (Wolkers and Hoekstra, 1995).…”
Section: Ftirmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these studies no explanation of the phenomenon of pollen injuries was proposed. Investigations of Hoekstra et al (1992), Wolkers and Hoekstra (1995) and Golovina et al (1998) showed that cytoplasmic membranes were prime targets for destructive changes in pollen grains as a result of abiotic stresses. There is little information in the literature about the structural and biophysical function of membranes in the tolerance of pollen grains to industrial pollution.…”
Section: Discussionmentioning
confidence: 99%